Pendampingan Pengelolaan Manajemen Waktu, Manajemen Keuangan, dan Manajemen Konflik bagi Ikatan Mahasiswa Tegal - Azmi, Muhammad Ulil; Fatmawati, Windy (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
Organizational assistance at the Tegal Student Association aims to guide and provide students with an in-depth understanding of the urgency and role of organizations. Through friendly activities, providing materials, discussions, and confirmation, mentoring is carried out for two days and one night for new students and administrators. The results show high student enthusiasm and their ability to overcome conflicts, challenges, and risks that arise. A good understanding of organizational goals enables program prioritization that is in line with the vision and mission. Mastery of the material creates a systematic management thinking framework, including time, financial, and conflict management. Students who are involved can actively contribute to organizations and the wider community.